Tanawwu‘ al-Lughāt: Kalimāt al-Nidā’ al-‘Arabīyah wa-Dukhūluhā fī al-Lughah al-Indūnīsīyah bi-Madīnat Medan - Nursukma Suri; Mascahaya; Farida Hanum Ritonga (Al-Ma‘rifah, 2019)
Arabic is one of the languages in the world that is used to interaction and communication, has the function to send messages and ideas. Arabic in Indonesia influences the vocabulary of the Indonesian language. With the absorption of the vocabulary of the language, it gives rise to a variety of languages. A variety of languages is a variant in a language that can be a dialect, style and even variations of the standard language. A variety of languages can be found in the form of verbal language that can be used in terms of address in the Arabic language. Terms of address in the Arabic language like ummi, abi, jid, jiddah, khale, khalati, amme, ammeh, ane, ente, antum, ustad, Muhammad, habib, bin, binti, akhi, ukhti, buya, and others. Besides that, the researcher also uses the Indonesian dictionary as a reference to see the term of address taken from Arabic. This research uses a survey or direct observation of the location also conducted a literature study on a variety of language: terms of address in the Arabic language in vocabulary developments of Indonesian language in the city of Medan.